Academic Climate and Classroom Facilities as Predictors of Learning Satisfaction: Testing a Motivational Mediation Model in Secondary Education - Rizal, Qomaruddin; Putra, Lisa Virdinarti (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
This study examines how academic climate and classroom facilities predict students’ learning satisfaction through the mediating role of learning motivation in secondary education. Using a quantitative cross-sectional design, data were collected from 290 students selected through proportional random sampling. Data were obtained using a self-report questionnaire based on a five-point Likert scale measuring students’ perceptions of academic climate, classroom facilities, learning motivation, and learning satisfaction, adapted from previously validated instruments in the literature. Structural path analysis with bootstrap resampling (5,000 samples) was employed to test direct and indirect effects. The results indicate that academic climate has a significant direct effect on learning satisfaction (β = 0.21, p < .01) and an indirect effect through learning motivation, indicating partial mediation. In contrast, classroom facilities do not directly predict learning satisfaction (β = 0.10, p > .05) but exert a significant indirect effect via learning motivation, indicating full mediation. Learning motivation emerges as the strongest predictor of satisfaction (β = 0.43, p < .001). The model explains 32% of the variance in learning motivation and 41% of the variance in learning satisfaction, demonstrating moderate explanatory power. These findings highlight that environmental quality influences students’ evaluative learning experiences primarily through motivational processes. Enhancing supportive academic climates and fostering motivational engagement may therefore be more impactful than infrastructural improvements alone in promoting sustainable student satisfaction.